Influence of γ-irradiation on kinetic effects in indium-alloyed cadmium antimonide single crystals - Koval, Yu.V. (Functional Materials, 2006)
Influence of γ-irradiation on the kinetic parameters of indium-alloyed cadmium antimonide single crystals has been studied. The conductivity and the Hall effect were measured, thus obtaining the dose and temperature dependences for concentration of charge carriers and their mobility. A sharp increase of charge carrier mobility has been found in the crystals irradiated at the doses up to 4•10¹⁸ γ-quanta per сm², which is explained by the presence of the "small dose effect ". It is noted that the increase of charge carrier mobility observed in this work is due not to the crystal ordering increase caused by the irradiation but to a decrease in the efficiency of charge carrier dispersion on ionic residues of the impurity during partial charge neutralization by the oppositely charged defects.